Optimization of pharmacotherapy in chronic heart failure: is heart rate adequately addressed? - Franke, Jennifer; Wolter, Jan Sebastian; Meme, Lillian; Keppler, Jeannette; Tschierschke, Ramon; Katus, Hugo; Zugck, Christian (Clinical research in cardiology, 2012)
The aim of the study is to evaluate the use of beta-blockers in chronic heart failure (CHF) and the extent of heart rate reduction achieved in clinical practice and to determine differences in outcome of patients who fulfilled select inclusion criteria of the SHIFT study according to resting heart rate modulated by beta-blocker therapy. We evaluated an all-comer population of our dedicated CHF outpatient clinic between 2006 and 2010. For inclusion, individually optimized doses of guideline-recommended pharmacotherapy including beta-blockers had to be maintained for at least 3 months and routine follow-up performed at our outpatient CHF-clinic thereafter. Treatment dosages of beta-blockers, and demographic and clinical profiles including resting heart rate were assessed. The outcome of patients who fulfilled select inclusion criteria of the SHIFT study (left-ventricular ejection fraction (LVEF) ≤35 %, sinus rhythm, NYHA II-IV) and were followed-up for at least 1 year was stratified according to resting heart rates: ≥75 versus <75 bpm and ≥70 versus <70 bpm. The composite primary endpoint was defined as all-cause death or hospital admission for worsening heart failure during 12-month follow-up. In total, 3,181 patients were assessed in regard to treatment dosages of beta-blockers, and demographic and clinical profiles including resting heart rate. Of the overall studied population, 443 patients fulfilled all inclusion criteria and entered outcome analysis. Median observation time of survivors was 27.5 months with 1,039.7 observation-years in total. Up-titration to at least half the evidence-based target dose of beta-blockers was achieved in 69 % and full up-titration in 29 % of these patients. Patients with increased heart rates were younger, more often male, exhibited a higher NYHA functional class and lower LVEF. The primary endpoint occurred in 21 % of patients in the ≥70 bpm group versus 9 % of patients in the group with heart rates <70 bpm (p <0.01). Likewise, comparing the groups ≥75 and <75 bpm, the primary endpoint was significantly increased in the group of patients with heart rates ≥75 bpm 27 vs. 12.2 %; p < 0.01). 5-year event-free survival was significantly lower among patients with heart rates ≥70 bpm as compared to those with <70 bpm (log-rank test p < 0.05) and among patients in the ≥75 bpm group versus <75 bpm group (log-rank test p < 0.01). In conclusion, in clinical practice, 53 % of CHF patients have inadequate heart rate control (heart rates ≥75 bpm) despite concomitant beta-blocker therapy. In this non-randomized cohort, adequate heart rate control under individually optimized beta-blocker therapy was associated with improved mid- and long-term clinical outcome up to 5 years. As further up titration of beta-blockers is not achievable in many patients, the administration of a selective heart rate lowering agent, such as ivabradine adjuvant to beta-blockers may pose an opportunity to further modulate outcome.
Gesehen am 24.04.2018